Rangeland and Pover~y Alleviation - Zhang, Qiaoyun; Shi, Minjun (Annals of Arid Zone, 2016)
This paper focuses upon rangeland degradation control and poverty alleviation, for a better understanding of the relationship' between rangeland management 'and poverty alleviation. Research results have shown no clear and unequivocal link between poverty and environment degradation. Different understandings of link between poverty and environment lead to different policy implications on poverty alleviation and environmental degradation control. It is important to understand what factors drive households' behavior and then to focus effort on these on a local level. Part of evidences show that agricultural intensification may contribute fan"geland degradation control. Combination of rural development policy and implementation of rangeland conservation regulation is an effective way to promote simultaneously rangeland conservation and poverty alleviation in developing countries. Key words: Rangeland management, poverty alleviation, rangeland conservation regulation, agricultural intensification.